Mboho Oi Ndeu Tradition Process in the Bima Community from an Islamic Cultural Perspective - Abu Haif; Muhammad Rifky Akbar Sahrul; Rifda Nur Amalina; Wihdatul Nisa (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The mboho oi ndeu tradition is one of the threads of the Bima Community wedding process, a tradition that has long been carried out by our ancestors. The Bima people know the marriage process with the term NIKA RA NEKU, in which there is a structure of traditional processes that must be carried out by the prospective bride and groom as follows: panati, ngge'e nuru, wa'a co'i mbolo weki, tek ra ne'e, Peta Kapanca, lafa nika (marriage contract), Mboho oi ndeu. The shift in this traditional procession has shifted along with social changes such as the development of industrial and information technology and local communities who have other activities, so that the traditional process no longer uses energy (non-material). but in its implementation, it is replaced by money (material) in each implementation. Therefore, researchers here want to study one of the processes of implementing Bima Community wedding customs, namely the Mboho Oi Ndeu process. This article will explain how the Mboho Oi ndeu traditional tradition is related to the history of Islamic culture, where in general the Bima people are predominantly Muslim and every Islamic value is carried out in life, blending with local culture. This research is descriptive in nature, using qualitative methodology. This method is used to easily explain a phenomenon that occurs in the Bima community, especially by using cultural studies.